METHODS OF FORMING STUDENTS NATURAL SCIENCE LITERACY IN CHEMISTRY LESSONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In recent years, the Uzbek  education system, as in the whole world is undergoing major changes, the new responsible approach is the need of continuous self-education for young people in secondary schools, mastering new information technologies, ability to cooperate and work in groups. These changes require some revision of both the content of training and approaches to identifying its effectiveness.